Android apps development for image processing - Wong, Thong Yau (Nanyang Technological University, 2023)
The exponential growth in smartphone usage can be traced back to June 29, 2007, when Apple officially launched the first smartphone, the iPhone. Since then, many smartphone companies have released their own mobile devices, such as smartphones and tablets, leading to a massive increase in mobile traffic.